Dialysis adequacy of chronic hemodialysis patients in Zanjan-Iran, 2016 - Yosefi Kh; Dinmohammadi MR; Moosaeifard M; Faghihzadeh S (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Dialysis adequacy is one of the most important factors in determining the survival rate and mortality of dialysis patients. Objectives: The aim of this study was to determine the dialysis adequacy of patients undergoing chronic hemodialysis at dialysis centers located in the province of Zanjan, located in northwest Iran. Methods: This descriptive cross-sectional study was performed on 257 patients undergoing chronic hemodialysis with an available sampling method in 6 dialysis centers in the province of Zanjan. The hemodialysis sessions were performed for 3 to 4 hours using via synthetic filters and bicarbonate dialysate. To determine the adequacy of dialysis, serum BUN levels were assessed before and after dialysis. The standard software provided by the Ministry of Health was used to calculate the adequacy of dialysis and Kt/V was considered to be at least 1.2. Results: The most common underlying causes of chronic dialysis were hypertension (41.2%) and diabetes mellitus (35.8%), respectively. Mean Kt/V and URR were 1.26±0.34 and 63.55±9.5%, respectively. The difference among these indexes was significant between men and women (p<0.05). Also, dialysis adequacy was significantly associated with increased dialysis frequency, blood flow rate, interdialytic weight gain, vascular access and dialysis shift (p<0.05). Conclusion: Despite the relatively favorable dialysis adequacy among patients, this index is highly variable based on patient gender, the dialysis center, location, frequency of dialysis, blood flow rate, interdialytic weight gain, type of vascular access and dialysis shift. Therefore, serious attention and greater caution are recommended among the dialysis centers of the province.